Tourists' perceptions of the religious tourism quality services: Gap Analysis Approach - Syarifudin, Efi; Anam , Khaerul (Universitas Negeri Surabaya, 2023)
This study aims to determine and analyze the perception of Muslim tourists on the services provided by the management of religious tourism, as well as what service indicators should be the main priority and maintained in providing full service to tourists. Importance and Performance Analysis (IPA) is the quantitative analysis approach used in this study. This analysis finds that tourist perceptions and preferences have an average degree of fit at 96%, indicating that the level of satisfaction with the quality of religious tourism services is relatively high. Furthermore, based on the study of the Cartesian diagram, two indicators demand more attention due to poor performance, i.e., (a) officers' response to tourist needs and (b) their competency to carry out their duties properly. Generally, visitors have given positive feedback, so management must maintain facilities and services.